(untitled) (Green University Review of Social Sciences, 2022)
In this modern era of digitalization, connecting people virtually is a state-of-the-art concept and demand of the time. Changing era demands improvisation of technologies and we must change not only to survive, but also to thrive. Besides, due to this unprecedented pandemic situation, online classes have become an indispensable part of teaching and learning system across the globe. However, every coin has its flip part and every benefit comes with its own limitation and online classes face some difficulties as well. Both the teachers and the students are going through novel online experiences either beneficial or challenging for them. Thus, by embracing the benefits and overcoming the obstacles all the stakeholders of teaching learning system can achieve their goals. In this paper, a study has been done with teachers and studentsthrough questionnaire survey. The purpose of this research is to study the benefits and challenges of online classes during Covid-19 pandemic at tertiary level in Bangladesh. The results suggest that, all the benefits and challenges discussed in the article are relevant and create impacts online classes. Besides, from the open-ended question asked to the teachers and the students, the research also provides some suggestions and recommendations to bring about some positivechanges the online classes. Green University Review of Social Sciences Dec 2021; 7(1-2): 208-219